Brazilian Adolescents' Body Weight Misperception and the Human Development Index of the Cities Where They Live. Issue 2 (April 2014) - Silva, Diego A. S.; Gonçalves, Eliane C. A.
This study investigated the relationship between adolescents' body weight misperception and the Human Development Index (HDI) of the cities in which they live in Brazil. Data from a large national survey that included 60, 973 boys and girls between 13 and 15 yr. ( M = 14.2, SD = 1.1; 47.5% boys, 52.5% girls) were analyzed. Regression analyses were adjusted for potential confounding factors such as population density, income inequality, nutritional status (BMI), and mothers' education. In both sexes, the relationship between perceived underweight showed an inverse relationship with HDI. The highest prevalences of participants who perceived themselves as overweight for girls were found in cities with high HDI.